1993
DOI: 10.1679/aohc.56.353
|View full text |Cite
|
Sign up to set email alerts
|

Migration of LHRH Neurons Derived from the Olfactory Placode in Rats.

Abstract: Using the olfactory placode of 12.5-and 14.5-day-old (E12.5, E14.5) rat embryos, we examined the migration of LHRH neurons by in vivo intraventricular transplantation and in vitro organotypic culture systems. In the transplantation, the olfactory placode of E12.5 embryos was co-transplanted with the cerebral cortex and also with medial basal hypothalamus (MBH). LHRH neurons that had migrated into the co-trans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…Nevertheless, although we have expected that the NAP tissue cultured in the present study does not contain components of the GnRH pulse generator other than GnRH neurons, it cannot be denied that other neurons, except for GnRH neurons, contributed to the generation of pulsatile GnRH release. In fact, we found synaptic junctions between GnRH neurons and unidentified neuronal processes in the terminal ganglion and in the septum of 16.5-day-old rat embryos [22]. Similar synaptic junctions were also seen in 7-day cultured VNO of 13.5-day-old rat embryos [Daikoku, unpubl.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, although we have expected that the NAP tissue cultured in the present study does not contain components of the GnRH pulse generator other than GnRH neurons, it cannot be denied that other neurons, except for GnRH neurons, contributed to the generation of pulsatile GnRH release. In fact, we found synaptic junctions between GnRH neurons and unidentified neuronal processes in the terminal ganglion and in the septum of 16.5-day-old rat embryos [22]. Similar synaptic junctions were also seen in 7-day cultured VNO of 13.5-day-old rat embryos [Daikoku, unpubl.…”
Section: Discussionmentioning
confidence: 74%
“…To date, primary cell cultures of GnRH neurons derived from embryonic olfactory placode have been performed in mice [21], rats [22], rhesus monkeys [23], and sheep [24]. Quite recently, it was reported that the cultured olfactory placode of rhesus monkeys releases GnRH in a pulsatile fashion [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that the embryonal medial basal hypothalamus (MBH), co-cultured with the vomeronasal organ (VNO), stimulates the development and migration of LHRH neurons from the VNO. However, coculturing with the olfactory cortex, the septo-preoptic area or the cerebral cortex showed no such stimulatory activities (DAIKOKU et a!., 1993). Further, we found in vivo that most of the hypothalamic peptidergic neurons differentiate around Day 18.5 of gestation (E18.5), and that LHRH neurons establish migration to the septopreoptic area project to the median eminence on E18.5 in rats (DAIKOKU et al, 1989).…”
mentioning
confidence: 67%
“…Insulin-like growth factor I mRNA and nerve growth factor mRNA were detected in the fetal rat hypothalamus (BACH et al, 1991;OJEDA et al, 1991). In a previous study, we found that the medial basal hypothalamus co-cultured with the vomeronasal organ had stimulatory effects on the development of LHRH neurons (DAIKOKU et al, 1993). As is currently accepted, neuronal growth and survival depend on largely target-derived factors (LEIBROCK et al, 1989;DAVIES,1994;LINDEN, 1994;LINDSAY et al, 1994).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation